Should women scientists really have to know how to bake cakes and knit to become leaders? - Davies, Amanda; Nash, M.; McLean, N. (2016)
The importance of helping women train for leadership roles has been widely acknowledged. But right now, we’re being kept out thanks to the prohibitive costs of getting there, write Dr Amanda Davies, Dr Meredith Nash and Nina McLean.